Pemberdayaan Masyarakat untuk Pencegahan Stunting dalam Rangka Membangun Masa Depan Masyarakat Unggul - Hidaytillah, Yetti; Misbahudholam AR, Muhammad; Rohmah, Afifah Afra; Mahtum, Ahmad Rahiqim; Badruttamam, Badruttamam; Abd. Mu’in, Abd. Mu’in; Praseno, Donny; Alifi, Wildan (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Community empowerment in preventing stunting must involve various parties, including local government, health workers, community leaders and families. This can be done by increasing access to quality health, nutrition and sanitation services in Aenganyar village. Health workers also have an important role in community empowerment. They can provide education and training to the public about the importance of balanced nutrition, the introduction of MP-ASI, and the importance of a healthy diet. Apart from that, they can also monitor and evaluate the nutritional status of children in Aenganyar village. Families need to realize the importance of preventing stunting and adopting a healthy and nutritious diet for their children. In addition, they need to access health services related to stunting prevention, such as immunization, exclusive breastfeeding and complementary feeding. By making efforts to empower the community in preventing stunting in Aenganyar village, it is hoped that it can reduce the prevalence of stunting in the area. This has a positive impact on the growth and development of children in Aenganyar village, as well as improving their quality of life and future.